2015
DOI: 10.1093/qjmed/hcv205
|View full text |Cite
|
Sign up to set email alerts
|

Sexual practices, myths and misconceptions among long distance truck drivers in North India

Abstract: Owing to continuing prevalence of such sexual myths, long distance truck drivers and helpers do not use condoms while having sex with CSW's as they feel that they can enjoy sex with CSW's and still stay protected against STD's/HIV. It is imperative that this battery water/urine antiseptic myth be specifically targeted for better HIV control in this high risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…Some studies have reported a high prevalence of sexual risk behavior in this group including sexual multiple partners and low rates of consistent condom use [ 3 8 ]. In fact, in North India, recent findings have shown that almost 30% of drivers and 50% of helpers didn’t use condom when having sexual contact with commercial sex workers [ 7 ], exposing themselves to HIV infection. In 2012, a study conducted on the main roads in Uganda reported that only 21% of truck drivers have consistently used condoms during sexual intercourse during their journeys [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported a high prevalence of sexual risk behavior in this group including sexual multiple partners and low rates of consistent condom use [ 3 8 ]. In fact, in North India, recent findings have shown that almost 30% of drivers and 50% of helpers didn’t use condom when having sexual contact with commercial sex workers [ 7 ], exposing themselves to HIV infection. In 2012, a study conducted on the main roads in Uganda reported that only 21% of truck drivers have consistently used condoms during sexual intercourse during their journeys [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although through television and radio their trucks are equipped with, some are aware of HIV/AIDS, however, there is high degree of misconception about the disease especially the mode of transmission which some believed is transmitted via mosquito bites, use of public toilets, bodily contact with people living with the virus/disease, sex with young commercial sexual worker's was less likely to cause sexually transmitted diseases (STDs) and HIV, use of battery water or urine antiseptic immediately after sex [28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nesse sentido, a população de caminhoneiros tem sido apontada em diferentes regiões do mundo como uma população com maior risco de adquirir o HIV, devido a algumas características laborais peculiares, como a mobilidade por rotas de longa distância e não permanência em suas cidades de origem 3 , principalmente em regiões do continente africano [9][10][11][12] e asiático [13][14][15][16] .…”
Section: Introductionunclassified
“…Comumen-te, os caminhoneiros são descritos na literatura como indivíduos que se relacionam com parceiras eventuais durante as viagens de longa distância 9,15,17,18,22 . Estudos também têm apontado para existência de fatores, significados e concepções que apoiam a não utilização do preservativo nas relações sexuais desses sujeitos com suas parceiras 12,15,16,22 . De acordo com Leal 18 , muitos dos estudos com esta população foram orientados pela metodologia de aferição de Conhecimentos, Atitudes e Práticas (chamados de CAP, ou KAP em Inglês), que possuem um enquadramento teórico-analítico orientado para o risco.…”
Section: Introductionunclassified